Dispute Settlement Method for Lending in Supply Chain Financial Technology in Indonesia - Trisadini Prasastinah Usanti; Fiska Silvia; Anindya Prastiwi Setiawati (International Journal of Supply Chain Management, 2020)
Abstract— Recently, in response to the credit crunch and the increased costs of financing, new solutions for supporting the financial management of supply chains, known as supply chain finance (SCF), have been developed. The purpose of this research is to analyze how the dispute raised from the situations faced by people who involved in fintech peer to peer lending can be solved in fairness. The methodology used in this research are statute approach, conceptual approach, and comparison dispute settlement among Australia and Indonesia through law case study. According to the Indonesian Law as it is stated in BW (Civil Code for Indonesia), companies can settle their loan disputes by filing a lawsuit to the district court. This method is less effective because it is time consuming and costly, while it is not worth with the nominal value of the loan which is not that much. This situation leads to a demand of a faster, simpler and low-cost solution that can be accessed online. This method is called as small claim court method. This method is considerably new and basically is a simplified procedure of the existing dispute settlement. A strong note on this method is its weakness when the disputes happen cross-border. This aspect needs to be improved in many ways considering the current method is only applicable when the parties have the same judicial territory. Hopefully, the information technology strongly supports the task of the judiciary in order to enforce law and legal justice through the application of Electronic Court (e-court) which is in line with the principle of simple, fast and low cost of justice. Vice versa, fintech lending dispute resolution requires procedural law that can compensate for the technology that is developing rapidly. The information technology management referred to information management policies, institutional information management institutional arrangements, and electronic system structuring at the Supreme Court.